Picking the Poor : Indicators for Geographic Targeting in Peru - Schady, Norbert R. (World Bank, Washington, DC, 2014)
Geographic targeting is perhaps the most popular mechanism used to direct social programs to the poor in Latin America. The author empirically compares geographic targeting indicators available in Peru. He combines household-level information from the 1994 and 1997 Peru Living Standards Measurement Surveys and district-level information from the 1993 Peru Population and Housing Census. He then conducts a series of simulations that estimate leakage rates; concentration curves; the impact of transfers on poverty as measured by the headcount index, poverty gap, and [poverty] measures of the Foster-Greer-Thorbecke family; and nonparametric (kernal) densities when transfers are based on alternative indicators. He concludes that there is substantial potential for geographic targeting in Peru. The differences in outcomes across geographic targeting indicators are small and not statistically significant.